Pathogenic NR2F1 variants cause a developmental ocular phenotype recapitulated in a mutant mouse model. Issue 3 (20th July 2021) - Jurkute, Neringa; Bertacchi, Michele; Arno, Gavin; Tocco, Chiara; Kim, Ungsoo Samuel; Kruszewski, Adam M; Avery, Robert A; Bedoukian, Emma C; Han, Jinu; Ahn, Sung Jun; Pontikos, Nikolas; Acheson, James; et al.
Abstract: Pathogenic NR2F1 variants cause a rare autosomal dominant neurodevelopmental disorder referred to as the Bosch–Boonstra–Schaaf Optic Atrophy Syndrome. Although visual loss is a prominent feature seen in affected individuals, the molecular and cellular mechanisms contributing to visual impairment are still poorly characterized. We conducted a deep phenotyping study on a cohort of 22 individuals carrying pathogenic NR2F1 variants to document the neurodevelopmental and ophthalmological manifestations, in particular the structural and functional changes within the retina and the optic nerve, which have not been detailed previously. The visual impairment became apparent in early childhood with small and/or tilted hypoplastic optic nerves observed in 10 cases. High-resolution optical coherence tomography imaging confirmed significant loss of retinal ganglion cells with thinning of the ganglion cell layer, consistent with electrophysiological evidence of retinal ganglion cells dysfunction. Interestingly, for those individuals with available longitudinal ophthalmological data, there was no significant deterioration in visual function during the period of follow-up. Diffusion tensor imaging tractography studies showed defective connections and disorganization of the extracortical visual pathways. To further investigate how pathogenic NR2F1 variants impact on retinal and optic nerve development, we took advantage of an Nr2f1 mutant mouse disease model. Abnormal retinogenesis in early stages of development was observed in Nr2f1 mutant mice with decreased retinal ganglion cell density and disruption of retinal ganglion cell axonal guidance from the neural retina into the optic stalk, accounting for the development of optic nerve hypoplasia. The mutant mice showed significantly reduced visual acuity based on electrophysiological parameters with marked conduction delay and decreased amplitude of the recordings in the superficial layers of the visual cortex. The clinical observations in our study cohort, supported by the mouse data, suggest an early neurodevelopmental origin for the retinal and optic nerve head defects caused by NR2F1 pathogenic variants, resulting in congenital vision loss that seems to be non-progressive. We propose NR2F1 as a major gene that orchestrates early retinal and optic nerve head development, playing a key role in the maturation of the visual system. Abstract : Jurkute et al. expands the phenotypic spectrum of pathogenic NR2F1 variants, providing a detailed characterization of the retinal and optic nerve changes with high-resolution optical coherence tomography imaging. Data from a mutant mouse model confirms the key role played by NR2F1 in directing retinogenesis and the development of the optic nerve head. Graphical Abstract: